The Manichaean Church at Kellis Social Networks and Religious Identity in Late Antique Egypt - Fiane Teigen, Håkon (Nag Hammadi and Manichaean Studies, 2021)
The Manichaean Church in Kellis presents an in-depth study of social organisation within the religious movement known as Manichaeism in Roman Egypt. In particular, it employs papyri from Kellis (Ismant el-Kharab), a village in the Dakhleh Oasis, to explore the socio-religious world of lay Manichaeans in the fourth century CE. Manichaeism has often been perceived as an elitist, esoteric religion. Challenging this view, Teigen draws on social network theory and cultural sociology, and engages with the study of lived ancient religion, in order to apprehend how laypeople in Kellis appropriated Manichaean identity and practice in their everyday lives. This perspective, he argues, not only provides a better understanding of Manichaeism: it also has wider implications for how we understand late antique 'religion' as a social phenomenon Readership: All interested in the history of Manichaeism, in late antique religion and religious change in the Roman Empire, the application of sociological theory to papyri, and the archaeology of Kellis.